(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article discusses the effective use of audiovisual materials in the classroom in the study of English as a second language.The audio-visual materials are a great help in stimulating and facilitating the learning of a foreign language. Making use of audio-visual allows teachers to diversify their lectures, display more information, and enhance students’ speaking also listening skills. 41